Climate and vegetation changes recorded in the post Holsteinian lake deposits at Ossówka (eastern Poland) - Bińka, Krzysztof; Szymanek, Marcin; Nitychoruk, Jerzy (Acta Geologica Polonica, 2023)
Due to the long sedimentation period (about 70 000 y.) and the unique quality of the lake deposits represented by very long, monotonous layers of lacustrine chalk, the sequence at Ossówka is exceptional. We conducted highly-resolved pollen and isotope analysis of the 27-m-long, upper part of the sequence of the lake sediments covering the final stage of the Holsteinian and the early phases of the Saalian Complex (Marine Isotope Stages (MIS) 11–10). In the pollen profile three main forest interstadials (L PAZ O-3, O-5, O-7) and the intervening steppe – tundra stadials (L PAZ O-2, O-4, O-6, O-8) as well as numerous units of lower rank were identified. Interstadials were characterized mainly by the presence of well-established pine forest. Stadials in turn, represented steppe – tundra vegetation with very pronounced continental influences. Also, three clearly established phases of forest fires starting at the beginning of interstadials and gradually disappearing are interesting feature of the sequence. Fires of that scale are very rarely noted in the palynological spectra. The examined sequence is characterized by the high dynamics of changes in the post interglacial part of the profile. It provides, coupled with clear features of the Holsteinian succession and its duration, a reliable correlation with other terrestrial and marine archives.
Keywords: pollen analysis; lake deposits; Saalian; Holsteinian